Soybean maturity and environmental effects in savanna systems; I: dry matter accumulation - Singh, A.; Carsky, R.J.; Lucas, E.; Dashiell, Kenton E. (Informa UK Limited, 2002)
Growing soybean varieties with high residue yield may help to sustain the soil organic matter (SOM) content when recycled. Replicated field trials were conducted in four Guinea savanna sites in Nigeria to study the dry matter partitioning in six soybean genotypes and evaluate them for biomass production. The varieties were early TGx1485-1D and late TGx1670-1F in Trial 1 and early TGx1485-1D, TGx1805-2E and TGx1681-3F, medium TGx1809-12E and late TGx923-2E and TGx1670-1F in Trial 2. On average, the proportion of total dry matter accumulated in soybean plant parts was 42% in grain, 36% in stover, 12% in leaf litter and 11% in roots and nodules. While maturity class had no significant effect on the grain yield of soybean, significantly higher dry matter accumulation of roots and nodules, leaf litter, and stover was observed in medium and late varieties compared with early varieties (P < 0.05). Thus, medium and late varieties would be better able to sustain the SOM content than early varieties when the residues are recycled. Strongly acid soils in a high rainfall environment limited soybean biomass production and potential to maintain SOM.